Improvement Knowledge and Attitude about Adolescent’s Reproductive Health through Education Intervention in Junior and Senior High: Peningkatan Pengetahuan dan Sikap tentang Kesehatan Reproduksi Remaja melalui Intervensi Penyuluhan pada Siswa Sekolah Menengah Pertama dan Sekolah Menengah Atas Negeri - Amiruddin Amiruddin; Sriyana Herman; Hermanto T. Joewono; Asrul Sani; Junaid Junaid; Ali Imran; Jafriati Jafriati (Indonesian Journal of Obstetrics and Gynecology, 2019)
Abstract Objective:To determine the changesin point of view and positive attitudes towards adolescent reproductive health in junior and senior high school students in Southeast Sulawesi after counseling interventions. Methods: Experimental Research with The One Group Pretest-Posttest Design. The population in the study were all adolescents aged between 12-19 years as students in Southeast Sulawesi. The sampling was performed by Simple stratified random sampling technique with a sample of 300 people for middle and high school students. The instrument used was a questionnaire with data analysis by using the t-test. Results:Showed that the level of knowledge and attitudes of students about adolescent reproductive health was differed between pretest & posttest in junior and senior high school students (Ï<0.05),because the students who were given counseling interventions with lecture methods, powerpoint, and discussion, will add to the broader understanding and insight and tend to generate positive responses from studentsm so that they have good basic knowledge and attitudes about adolescent reproductive health. Conclusion:The study was the increase in knowledge and positive attitudes about adolescent reproductive health after counseling interventions. Keywords:adelescent, counseling, knowledge and attitude, reproductive health Abstrak Tujuan:Untuk mengetahui perubahan pengetahuan dan sikap yang positif tentang kesehatan reproduksi remaja pada siswa SMP dan SMA Negeri di Sulawesi Tenggara setelah dilakukan intervensi penyuluhan. Metode: Penelitian Eksperimen (pre-experiment) dengan rancanganThe One Group Pretest-Posttest Design. Populasi dalam penelitian adalah keseluruhan remaja yang berusia antara 12-19 tahun yang sementara berstatus sebagai siswa SMP dan SMA Negeri di Sulawesi Tenggara. Pengambilan sampel dilakukan dengan teknikSimple stratified random sampling dengan jumlah sampel 300 orang untuk siswa SMP dan SMA.Instrumen yang dipakai adalah angket dengan analisis data menggunakan uji-t. Hasil:Menunjukkan tingkat pengetahuan dan sikap siswa tentang kesehatan reproduksi remaja berbeda antara pretest dan posttest pada siswa SMP dan SMA Negeri di Provinsi Sulawesi Tenggara (Ï value< 0,05).Hal ini disebabkan karena pada siswa SMP dan SMA Negeri di Provinsi Sulawesi Tenggara yang diberikan intervensi penyuluhan dengan metode ceramah, visualisasi (power point), dan tanya jawab, akan menambah pemahaman dan wawasan yang lebih luas dan cenderung menimbulkan respon yang positif dari siswa sehingga memiliki pengetahuan dan sikap yang baik tentang kesehatan reproduksi remaja. Kesimpulan:Terjadi peningkatan pengetahuan dan sikap yang positif tentang kesehatan reproduksi remaja setelah intervensi penyuluhan. Kata Kunci:remaja,penyuluhan, pengetahuan dan sikap, kesehatan reproduksi